Multiple mutations in heterogeneous miltefosine-resistant Leishmania major population as determined by whole genome sequencing. - Adriano C Coelho; Sébastien Boisvert; Angana Mukherjee; Philippe Leprohon; Jacques Corbeil; Marc Ouellette (Public Library of Science (PLoS), 2012)
Miltefosine (MF) is the first oral compound used in the chemotherapy against leishmaniasis. Since the mechanism of action of this drug and the targets of MF in Leishmania are unclear, we generated in a step-by-step manner Leishmania major promastigote mutants highly resistant to MF. Two of the mutants were submitted to a short-read whole genome sequencing for identifying potential genes associated with MF resistance.Analysis of the genome assemblies revealed several independent point mutations in a P-type ATPase involved in phospholipid translocation. Mutations in two other proteins-pyridoxal kinase and α-adaptin like protein-were also observed in independent mutants. The role of these proteins in the MF resistance was evaluated by gene transfection and gene disruption and both the P-type ATPase and pyridoxal kinase were implicated in MF susceptibility. The study also highlighted that resistance can be highly heterogeneous at the population level with individual clones derived from this population differing both in terms of genotypes but also susceptibility phenotypes.Whole genome sequencing was used to pinpoint known and new resistance markers associated with MF resistance in the protozoan parasite Leishmania. The study also demonstrated the polyclonal nature of a resistant population with individual cells with varying susceptibilities and genotypes.